Risk-Based Communication Model for the Prevention of Serious Injuries and Fatalities at PT XYZ - Perie Anugraha Wiguna; Ari Hernawan (Jurnal KESANS : Kesehatan dan Sains, 2026)
Introduction: Serious injuries and fatalities (SIF) remain critical challenges in facility service operations, where risk messages often fail to translate into safe frontline behavior. Objective: This study aimed to develop and validate a risk-based communication model to strengthen safety awareness, assertive behavior, and SIF prevention at PT XYZ. Method: A descriptive qualitative applied design was used through field observation, in-depth interviews, focus group discussion, document review, and expert judgment. Supporting data included incident records, workforce demographics, safety climate indicators, and a risk communication questionnaire involving 100 respondents. Result and discussion: Findings showed that existing communication channels were mostly linear, administrative, and text-based, causing habituation, information overload, and weak personal risk appreciation. Key barriers included safety silence, high power distance, low assertiveness toward senior workers, and service pressure that encouraged out-of-scope work. The S-C-F model integrated Standardization through visual Scope of Work cards, Confidence through Stop Work Authority and DESC scripting, and Feedback Loop through check-back communication for non-routine work. Expert validation produced a mean feasibility score of 3.68, indicating a very feasible model. Conclusion: The S-C-F model is applicable for improving risk communication and preventing SIF in high-risk facility service operations